(untitled) (Eurasian Journal of Philology Science and Education, 2026)
The article examines the concept of digital linguodidactics and its role in the formation of new forms in the process of teaching the Kazakh language and Kazakh literature. In the context of the modern information society, the education system is developing in close connection with digital technologies. Therefore, the modernization of traditional methods of language education and their adaptation to the digital learning environment have become increasingly relevant. Digital linguodidactics is a scientific and methodological field that studies the effective use of information and communication technologies, digital platforms, interactive tools, and multimedia resources in language teaching. This direction contributes to the development of learners’ communicative, cognitive, and creative abilities. The study analyzes the potential of digital educational resources used in teaching the Kazakh language and literature. In particular, online platforms, mobile applications, virtual classrooms, podcasts, video lectures, interactive tasks, and artificial intelligence-based educational tools contribute to increasing the effectiveness of the language learning process. Such tools enhance students’ learning motivation and facilitate the perception and acquisition of linguistic material. Moreover, digital technologies make it possible to create individual learning trajectories, develop independent learning skills, and promptly assess learning outcomes. The article examines blended learning, distance learning, microlearning, digital storytelling, podcasting and gamification methods as new forms of teaching the Kazakh language and Kazakh literature. These approaches help organize the educational process as an interactive, dynamic, and learner-centered system. Digital linguodidactics also ensures the integration of textual, audio, and visual information in the learning process, forming a multi-channel perception of educational material. The study’s results demonstrate that digital linguodidactics can serve as an important scientific and methodological basis for modernizing Kazakh language and literature teaching methods. Effective use of digital technologies not only improves the quality of education but also allows for the adaptation of Kazakh language and literature teaching to modern educational requirements. Keywords: digital linguodidactics, teaching Kazakh language and literature, digital education, interactive learning, online platforms, digital resources, linguistic competence, innovative methods.